Concurrent Validity and Reliability of Two-dimensional Frontal Plane Knee Measurements during Multi-directional Cutting Maneuvers - Dimas Sondang Irawan; Chantheng Huoth; Komsak Sinsurin; Pongthanayos Kiratisin; Roongtiwa Vachalathiti; Jim Richards (International Journal of Sports Physical Therapy)
# Background